Death in Patients with Regular Hemodialysis Due to CKD in RSUD Dr. Soedono Madiun Not Correlated to Various Risk Factors - Lumaksono, Tulus; Rachmawati, Anisa; Marfianti, Erlina (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2017)
Background: Chronic Kidney Disease (CKD) indicated by the inability of the kidneys in maintaining homeostasis of the body.1 This causes the patient to undergo renal replacement therapy for life. Patients undergoing regular hemodialysis have a higher risk of death in the last 2 decades. The survival of hemodialysis patients is different because it is influenced by several factors, including age, sex, duration of hemodialysis, duration of hemodialysis and accompanying comorbid patients.Objective: To identify risk factors that affect mortality in patients with CKD undergoing regular hemodialysis.Method: This research is an observational research with case-control design. Research done in dr.Soedono Madiun Hospital in December 2016 with a sample size of 41 cases and 41 control. Data retrieved through the medical records of patients with CKD who undergo regular HD from January to November 2016. Data analysis was performed including analysis of univariate, Â bivariate analysis using chi-square test with 95% CI, 5% significance level (Î± = 0.05) and analysis multivariste using logistic regression.Results: There was no significant relationship between age (p = 0.23; OR = 1.78; 95% CI 0.68 to 4.64), gender (p = 0.623; OR = 1.24; 95% CI 0, 49 to 3.18), long live HD (p = 0.12; OR = 0.50; 95% CI 0.20 to 1.20), duration of HD (p = 0.81, OR = 0.89; 95% CI 0.34 to 2.28), hypertension (p = 0.21; OR = 0.44; 95% CI 0.12 to 1.61), diabetes mellitus (p = 0.17; OR = 1 , 83, 95% CI 0.75 to 4.47), hemoglobin level (p = 0.26; OR = 1.66; 95% CI 0.68 to 4.05) and intradialitik complications (p = 0.81 , OR = 1.11; 95% CI 0.44 to 2.80) with mortality in patients with CKD.Conclusion: There is no significant relationship between age, gender, length undergoing hemodialysis, duration of HD, hypertension, diabetes, hemoglobin, and complications intradialitik in CKD patients undergoing hemodialysis in dr.Soedono Madiun Hospitals.Â Â